The Effect of Motivation and Work Environment on Employee Performance at PT. Pratama Savindo Oetama - Munaza Panggalih; Nur Asni Gani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the era of globalization, the role of Human Resources (HR) has become increasingly vital in ensuring organizational success. Companies must strategically manage HR by improving employee performance through motivation and a conducive work environment. However, performance indicators at PT. Pratama Savindo Oetama has shown a decline from 2021 to 2023, raising concerns about the effectiveness of current HR strategies. This study aims to analyze the influence of work motivation and work environment on employee performance at PT. Pratama Savindo Oetama. This research employed a quantitative descriptive approach involving 30 employees as respondents. Data were collected through questionnaires distributed via Google Forms, supported by observation and interviews. The analysis was conducted using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results show that work motivation has a negative and insignificant effect on employee performance (t-count = 1.181 < t-table = 2.051; sig. = 0.248 > 0.05), suggesting that current motivation strategies may be ineffective or misaligned with employee needs. Conversely, the work environment has a positive and significant effect on performance (t-count = 5.283 > t-table = 2.051; sig. = 0.001 < 0.05), indicating that a supportive environment enhances productivity. The findings recommend a reevaluation of motivational strategies and promote improving workplace conditions to boost performance.